2020
DOI: 10.3390/agriculture10100431
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Internet of Things Water Management for Efficient Rice Irrigation in Rwanda

Abstract: The central role of water access for agriculture is a clear challenge anywhere in the world and particularly in areas with significant seasonal variation in rainfall such as in Eastern and Central Africa. The combination of modern sensor technologies, the Internet, and advanced irrigation equipment combined in an Internet of Things (IoT) approach allow a relatively precise control of agricultural irrigation and creating the opportunity for high efficiency of water use for agricultural demands. This IoT approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Farmers need to learn a different fieldwork knowledge compare with their long-term experience and have a higher fieldwork load. Fortunately, based on the technology's development, several water-saving techniques based on rice production systems are established by advanced equipment and applications, e.g., Asnawi & Syukriasari (2019); Bamurigire, Vodacek, Valko, & Rutabayiro Ngoga (2020). However, these kinds of systems and related facilities typically come with a high price.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers need to learn a different fieldwork knowledge compare with their long-term experience and have a higher fieldwork load. Fortunately, based on the technology's development, several water-saving techniques based on rice production systems are established by advanced equipment and applications, e.g., Asnawi & Syukriasari (2019); Bamurigire, Vodacek, Valko, & Rutabayiro Ngoga (2020). However, these kinds of systems and related facilities typically come with a high price.…”
Section: Resultsmentioning
confidence: 99%
“…Levidow et al (2014) pointed out that a smart cultivation system provides farmers with a simple, instant, easy-to-use, free system to help farmers determine the daily irrigation amount and provide many crops possible to promote watersaving irrigation technologies and increase the utilization rate. Although there are many studies on developing and using Internet of Things (IoT) technology to help rice paddy field observation and automatic fieldwork operation, there only a few studies have been found integrating IoT and irrigation on an integer system (Bamurigire, Vodacek, Valko, & Rutabayiro Ngoga, 2020;Krishnan et al, 2020), especially in advanced Narrowband IoT (NB-IoT) technique and application guideline on watersaving irrigation. Due to the water-saving irrigation has considerable benefits to the environment and the income of farmers, this study is focusing on modern technology to develop paddy field observation equipment with smartphone-based real-time field data display system and cultivation calendar notification based on NB-IoT, to decrease the threshold for farmers to conduct water-saving irrigation technology.…”
Section: Introductionmentioning
confidence: 99%
“…Lu and Xie found that a labor shortage can exacerbate agricultural non-point source pollution caused by chemical fertilizer [5]. Additionally, a larger planting scale requires more efficient and labor-saving agricultural technologies [8]. Therefore, with as advantages its labor-saving characteristics and large-scale application, the Intelligent Irrigation Control System (IICS) has become a possible solution [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Internet of things technology develops quickly, and soil moisture sensor networks (SMWSNs) are already used in the actual production process. Moreover, the development of artificial intelligence, cloud computing, and big data has also greatly improved SMWSN efficiency [2][3][4]. However, due to the particularity of soil moisture sensors, the original evaluation mechanism for wireless sensor networks is not well applicable to SMWSNs, so it is urgent to propose a novel network efficiency evaluation mechanism [5].…”
Section: Introductionmentioning
confidence: 99%
“…(3) A quantum clone elite genetic algorithm (QCEGA) that combines the concepts of quantum computing and cloning is proposed. This algorithm can obtain the optimal target allocation method and has good convergence performance (4) The target allocation method based on QCEGA is compared with SA and PSO in terms of network efficiency, convergence performance, and computational complexity…”
Section: Introductionmentioning
confidence: 99%